Molecular detection of antimicrobial resistance in livestock mycoplasmas: current status and future prospects - Sulyok, Kinga M.; Kreizinger, Zsuzsa; Földi, Dorottya; Kovács, Áron Botond; Grózner, Dénes; Manso-Silván, Lucía; Bokma, Jade; Heuvelink, Annet E.; Klose, Sara M.; Feberwee, Anneke; Catania, Salvatore; Ramirez Corbera, Ana S.; et al. (Frontiers in Veterinary Science, 2025)
Pathogenic Mycoplasma species significantly impact livestock health, causing respiratory, articular, mammary gland, and reproductive disorders with substantial economic losses. Antimicrobials remain essential for controlling clinical signs and production losses; however, treatment efficacy is increasingly threatened by antimicrobial resistance (AMR). Phenotypic methods remain the most reliable approach for detecting AMR in Mycoplasma species; however, they are time-consuming, technically demanding, and results are often difficult to interpret. The absence of clinical breakpoints and limited epidemiological cut-off values (ECOFFs) further complicate AMR categorization. Advances in molecular techniques offer a promising alternative for faster AMR detection and prediction. This review summarizes current knowledge of genetic mechanisms underlying AMR in clinically important Mycoplasma species affecting ruminants, swine, and poultry. It highlights the role of molecular assays in identifying resistance-associated mutations. Additionally, a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis evaluates these methods’ practical applications and limitations in veterinary mycoplasmas. Finally, the potential of genome-wide association studies (GWAS) is explored as an emerging tool for linking genetic traits to phenotypic resistance patterns, offering new insights for enhancing resistance prediction in veterinary medicine.